Saint Odd - Koontz, Dean R. (Dean Ray), 1945- (New York : Bantam Books, 2015)
Two years after events that sent him journeying into mystery, Odd Thomas has traveled back to his home town of Pico Mundo where he prepares to confront the forces that arrayed against him.
Keywords: Thomas, Odd (Fictitious character) -- Fiction; Cooks -- Fiction; Mediums -- Fiction; Occult fiction; Suspense fiction